Checklist of the Argentine Agaricales 6. Paxillaceae, Gomphidiaceae, Boletaceae, and Russulaceae - Niveiro, Nicolás (2013)
A checklist of species belonging to families Paxillaceae, Gomphidiaceae, Boletaceae, and Russulaceae was made for Argentina. The list includes all species published up to 2011. Sixteen genera and 54 species are recorded: 15 species from Paxillaceae, 3 from Gomphidiaceae, 11 from Boletaceae, and 25 from Russulaceae.